Die karitative Tätigkeit im Schatten des Kommunismus in der VR Polen - Biel, Robert J. (European Journal of Mental Health, 2009)
Charitable Activities in the Shadow of the Communist System in the People’s Republic of Poland: In addition to liturgy and preaching, charity is one of the most important tasks of the Church. This holds true for the Polish Catholic Church as well, where benevolence has a longstanding tradition. An Episcopal Committee dealing with the affairs of victims of war was established as early as 1915 in Krakow, while only 7 years later, in 1922, the Caritas Association was set up. Before the Second World War, the Church in Poland was considered a major charitable institution. World War II wrote a strange chapter in the history of charitable activities of the Church in Poland. On 23 June 1940, the occupying German forces abolished all structures of Caritas. In their stead in 1940 they established the ‘RGO’ (Central Welfare Council) and the ‘PolKo’ (Polish Welfare Committees) that could provide charitable assistance. Right after the end of the war, in June 1945, the Polish Bishops’ Conference set up the national centre of Caritas, which immediately restarted its official activities. Not long after the change in power, communist attacks targeting the activities of Caritas started. The difficult times of communist persecution increasingly meant the obstruction of charitable Church activities, which were also manifested in various forms of charitable mental health care. As a result, by 1950, Caritas – along with its institutions – came under the forced control of the state. The national centre of Caritas had to be disbanded, and its assets were confiscated by the state authorities. Following the 1950 dissolution of the national headquarters of Caritas, the church organisation was replaced by the newly founded ‘Caritas Association of Catholics’ which answered to the communist government. In response, the Polish Bishops’ Conference established the National Secretariat for Charity Matters. The declaration of the state of emergency in 1981 also prompted the Church to step up its charitable activities. The 1980s saw a considerable surge in institutional charity work in Poland, when the social role of the Church broadened significantly in the growing economic crisis. The Charity Commission was convened in January 1981, and not long after the overthrow of communism, on 10 October 1990, following a 40-year hiatus, a church-run Caritas was established again, which today needs to be ready to deal with contemporary challenges like unemployment, social insecurity and emigration.